2018
DOI: 10.5935/1518-0557.20180047
|View full text |Cite
|
Sign up to set email alerts
|

The effects of male age on sperm DNA damage: an evaluation of 2,178 semen samples

Abstract: ObjectiveThis study aimed to evaluate the effects of male age on sperm DNA damage.MethodsThis cross-sectional study included semen samples collected from 2,178 men seen at an infertility clinic. For DNA integrity analysis, the proportions of spermatozoa showing DNA fragmentation (TUNEL assay), abnormal chromatin packaging/underprotamination (chromomycin A3), abnormal mitochondrial membrane potential (MMP/MitoTracker Green), and apoptosis (annexin V) were recorded. For group comparisons, enrolled subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
6
18
2
2
Order By: Relevance
“…More studies with greater numbers of normal fertile individuals must be performed to confirm the effects of aging on sperm concentration, total sperm count, sperm motility, and sperm DNA fragmentation. Nevertheless, the findings reported in this and other similar studies (Varshini et al, 2012;Stone et al, 2013;Oliveira et al, 2014;Gunes et al, 2016;Petersen et al, 2018) suggest that aging has a negative effect on most semen parameters and DNA integrity. Therefore, age is an important factor to consider in the treatment of infertile couples.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…More studies with greater numbers of normal fertile individuals must be performed to confirm the effects of aging on sperm concentration, total sperm count, sperm motility, and sperm DNA fragmentation. Nevertheless, the findings reported in this and other similar studies (Varshini et al, 2012;Stone et al, 2013;Oliveira et al, 2014;Gunes et al, 2016;Petersen et al, 2018) suggest that aging has a negative effect on most semen parameters and DNA integrity. Therefore, age is an important factor to consider in the treatment of infertile couples.…”
Section: Discussionsupporting
confidence: 41%
“…Other authors using the same technique described similar findings (Varshini et al, 2012;Oliveira et al, 2014). Petersen et al (2018) also concluded that DNA fragmentation worsened with age and associated it with mitochondrial damage, since mitochondrial membrane potentials deteriorate significantly with age. One might argue that it is advisable to assess older men seeking fertility treatment for DNA fragmentation, since it may cause infertility (Ahmadi et al, 2016) and increase miscarriage rates (García-Ferreyra et al, 2015).…”
Section: Discussionmentioning
confidence: 53%
“…Our study population was probably too small to adequately address the question of whether or not lifestyle factors, such as BMI, alcohol and smoking may also have an influence on acrosomal status. Male age has been found to have an effect on some of the classical sperm parameters and sperm DNA fragmentation [ 27 , 28 , 29 ]; however, we were not able to show a significant correlation between acrosomal status and the age of the male partner, which again may be due to the size of study population. The age of the female partner has a significant impact on the chances of pregnancy and also on the type of fertility treatment chosen [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Earlier studies on the importance of the acrosome are mainly related to the acrosomal responsiveness, i.e., the ability of the acrosome to react to stimuli, such as an ionophore or progesterone, and release its content by exocytosis [ 25 , 26 , 27 , 28 ]. Acrosomal responsiveness is, however, a different matter of concern as it only relates to the proportion of spermatozoa that still retain an intact acrosome.…”
Section: Discussionmentioning
confidence: 99%
“…С помощью метода TUNEL в ряде работ выявлена прямая зависимость уровня фрагментации ДНК от возраста мужчин [4][5][6][7], что согласуется с данными, полученными в нашем исследовании. Другие авторы не выявили кор реляции с целостностью хроматина сперматозоидов [8,9].…”
Section: Discussionunclassified